2019
DOI: 10.3389/fmicb.2019.02380
|View full text |Cite
|
Sign up to set email alerts
|

Tall Fescue and E. coenophiala Genetics Influence Root-Associated Soil Fungi in a Temperate Grassland

Abstract: A constitutive, host-specific symbiosis exists between the aboveground fungal endophyte Epichloë coenophiala (Morgan-Jones & W. Gams) and the cool-season grass tall fescue (Lolium arundinaceum (Schreb.) Darbysh.), which is a common forage grass in the United States, Australia, New Zealand, and temperate European grasslands. New cultivars of tall fescue are continually developed to improve pasture productivity and animal health by manipulating both grass and E. coenophiala genetics, yet how these selected grass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…These studies suggest that this inhibition is caused by endophyte presence and its impact on the competitive ability of the host grass. This is problematic because the endophytes can modify multiple host traits that can alter the success of legumes and their interaction with rhizobia and AMF (García-Parisi et al, 2015Slaughter et al, 2016Slaughter et al, , 2019Vignale et al, 2016). Therefore, it is essential to study the mechanisms by which the grass-endophyte symbiosis can inhibit the establishment of a legume.…”
Section: However This Classification Allows Us To Understand What Happensmentioning
confidence: 99%
“…These studies suggest that this inhibition is caused by endophyte presence and its impact on the competitive ability of the host grass. This is problematic because the endophytes can modify multiple host traits that can alter the success of legumes and their interaction with rhizobia and AMF (García-Parisi et al, 2015Slaughter et al, 2016Slaughter et al, , 2019Vignale et al, 2016). Therefore, it is essential to study the mechanisms by which the grass-endophyte symbiosis can inhibit the establishment of a legume.…”
Section: However This Classification Allows Us To Understand What Happensmentioning
confidence: 99%
“…Beyond Epichloë , research into associations between fungi and tall fescue has typically focused on fungal pathogens [ 9 , 12 , 13 , 14 , 15 , 16 ], soil fungi [ 17 , 18 , 19 ], and root fungi such as arbuscular mycorrhizal fungi (AMF) and dark septate endophytes [ 20 , 21 , 22 , 23 , 24 , 25 ]. Many (although not all, see [ 16 , 22 , 24 , 25 ]) of these studies also show correlations between Epichloë infection and the fungus being studied.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of studies have shown that endophyte infection can affect not only the growth and resistance of host plants but also the soil microbial community in host habitats such as AMF (Iqbal et al 2012;Slaughter et al 2019). Focusing on economically important cultivated grasses such as Lolium arundinaceum Darbyshire ex.…”
Section: Introductionmentioning
confidence: 99%